Supercritical water oxidation for the destruction of toxic organic wastewaters: A review - Veriansyah Barribang; Kim Jae-Duck (SCIENCE PRESS, 2007)
The destruction of toxic organic wastewaters from munitions demilitarization and complex industrial chemical clearly becomes an overwhelming problem if left to conventional treatment processes. Two options, incineration and supercritical water oxidation (SCWO), exist for the complete destruction of toxic organic wastewaters. Incinerator has associated problems such as very high cost and public resentment; on the other hand, SCWO has proved to be a very promising method for the treatment of many different wastewaters with extremely efficient organic waste destruction 99.99% with none of the emissions associated with incineration. In this review, the concepts of SCWO, result and present perspectives of application, and industrial status of SCWO are critically examined and discussed.
Keywords: WASTE-WATER; METHYLPHOSPHONIC ACID; MANUFACTURING PROCESS; SALT PRECIPITATION; HYDROGEN-PEROXIDE; SHAPE SELECTIVITY; AQUEOUS-SOLUTIONS; KINETIC-ANALYSIS; HIGH-TEMPERATURE; POROUS REACTOR